(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ayurveda comprises of a range of medicines including the fermented forms specifically Arishtas (fermented decoctions) and Asavas (fermented infusions). Lohasava are derivatives of primitive form of processing of iron i.e. Ayaskriti. The resemblance between the constituents of Lohasava shows the progressive development of Lauhakalpa basing upon fundamental principles of Rasashastra. In this paper details about Lohasava, their different pharmaceutical variations apart from other relevant information have been highlighted. This paper covers all the essential details of Asavarista (classification of Sandhana kalpana, Indication of Sandhana prakriya, S.O.P. For form of Iron to be used etc.) physicians to prescribe and a teacher to educate his pupils about Lohasava.